THE INFLUENCE OF E-TRUST, E-SERVICE QUALITY, PRICE AND WEB QUALITY ON TRAVELOKA USER E-SATISFACTION - Shahrul Wijayanto, Kukuh; Ibnu Fitroh Sukono Putra, Febrianur (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
The purpose of this investigation was to determine if a correlation exists between e-trust, e-service quality, price, and web quality in relation to traveloka user e-satisfaction. The methodology employed was quantitative and involved collecting survey data from 100 users of the traveloka app and website. Statistical analysis was performed utilizing SPSS V.24 software. The research utilized various tests including validity, reliability, normality, heteroscedasticity, multicollinearity, T-test, F-test, and coefficient of determination. The results demonstrate that e-trust, e-service quality, price, and web quality positively and significantly impact e-satisfaction. Notably, e-trust has a partially but significantly positive impact on e-satisfaction. Additionally, the quality of e-service and price variables significantly positively affect e-satisfaction, as well as web quality, which is another significant factor that positively influences e-satisfaction.